Engineering Novel CD19/CD22 Dual-Target CAR-T Cells for Improved Anti-Tumor Activity. (16th March 2022) - Zeng, Wanying; Zhang, Qing; Zhu, Yangmin; Ou, Ruiming; Peng, Liang; Wang, Baolei; Shen, Huijuan; Liu, Zhi; Lu, Lisheng; Zhang, Pumin; Liu, Shuang
Abstract: Despite high remission rates following chimeric antigen receptor T cell (CAR-T) cell therapy in B-cell acute lymphoblastic leukemia (B-ALL), relapse due to loss of the targeted antigen is increasingly recognized as a mechanism of immune escape. We hypothesized that simultaneous targeting of CD19 and CD22 may improve the CAR-T effect. The in vitro and in vivo leukemia model was established, and the anti-tumor effects of BiCAR-T, CD19 CAR-T, CD22 CAR-T, and LoopCAR6 cells were observed. We found that the BiCAR-T cells showed significant cytotoxicity in vitro and in vivo . The CD19/CD22 bivalent CAR provides an opportunity to test whether simultaneous targeting may reduce the risk of antigen loss.